Affecting Factors of the Performance of Employees in the Dr. H. Soemarno Sosroatmodjo Regional General Hospital Kuala Kapuas - Singgih Priono; Moh. Heru Budihantho; Septeria Noor Yuliannisa (East Asian Journal of Multidisciplinary Research, 2022)
The research that has been conducted aims to determine the factors that affect employee performance at the Dr. H. Soemarno Sosroatmodjo General Hospital Kuala Kapuas. The research was conducted using descriptive methods, data were collected and obtained from interviews, observations and documentation, data were collected through key informants and informants. The data that has been collected is analyzed by qualitative analysis. The research that has been done gives the results that the factors that affect the performance of employees at the Regional General Hospital Dr. H. Soemarno Sosroatmodjo Kuala Kapuas is seen from the ability which consists of education, the employees at the Regional General Hospital Dr. H. Soemarno Sosroatmodjo Kuala Kapuas mostly had high school education, especially structural ones. The training that employees participated in was secretarial training, budgeting, and equipment maintenance as well as financial accountability, and functional training aimed at medical personnel, especially nursing staff. H. Soemarno Sosroatmodjo Kuala Kapuas can be said to be good although there is still a need for guidance, the supervision carried out is informal, namely by providing only direction, the condition of facilities and infrastructure is still not adequate to support the work, and the physical condition of the work environment is still being improved.